Measuring success factors and performance of institutional repositories - Mohd Helmi Masor@Mansor; Norliya Ahmad Kassim (Universiti Sains Islam Malaysia, 2024)
The Institutional Repositories (IR) is a new scholarly communications platform in providing and disseminating digital contents of a university and academic institution. This study aims to measure the perceptions on six success factors of IR (knowledge sharing, self-archiving, IR usage, IR policy, IR procedure and copyright awareness) and IR performance among academicians in a Malaysian university and to seek the relationship between success factors of IR and IR performance. A set of questionnaire was distributed to selected academicians in one large faculty of information management in a Malaysian university. The results found that self-archiving, IR policy and IR procedure are the most preferred response by the respondents while it was also revealed that IR policy was positively and strongly correlated with IR procedure. The existence of strong relationship between IR policy and IR procedure shows that positive perceptions will help to enhance the IR performance. The result is significant to the academic libraries in enhancing their repository services and measuring the performance of the university’s research activities.